¿Incapaces de Dios? - Moros Claramunt, Enrique R. (Scientia et Fides, 2021)
Are we Human Beings Unable of God? José Cobo maintains that the worldview of contemporary man does not allow him to believe in the sense that the first Christians believed. And he argues that the main cause of that vision has been the development of empirical science. Here I argue that in reality the cause can best be described as an anthropological error, which carries with it a metaphysical deficit. On the other hand, we rectify certain intellectual resources with which we intend to get out of this situation.